دور السياحة في تنمية المجتمع المحلي . - درابلية, مروة (جامعة الوادي- University of Eloued, 2017)
Tourism is one of the economic activities of great importance in the world, and it is based on the economies of many countries, which stems from the status that reached it as an industry that has its own inputs and outputs, which made it a major source of income in many countries of the world, One of the fastest growing industries in terms of achieving growth rates, so we will try through this paper to exposure to the subject of tourism and its role in the development of local, whether on the economic, social or cultural
The role of tourism in local community development.
مقال
Keywords: tourism, development, community, local development.